Relationship between physical activity levels and physical fitness of young (15-17 ages) - Adem Cıvan; Nesrin Sayın (Selcuk University, 2017)
The aim of this study was to investigate the relation between physical activity levels and physical fitness of young people (aged 15-17). In total, 200 students participated in this study voluntarily. Physical activity levels were determined by the application of International Physical Activity Questionnaire to the participants. Body composition was also determined by the Body Mass Index calculation. V sit - reach test, 30 seconds sit-up test, 20 meters sprint, 1 mile run and walk test, standing long jump and medicine ball throw tests. The MET scores were calculated for the determination of physical activity levels. The relation with physical fitness was determined by the Pearson correlation test (p lt;0.05). It was found that the male was physically more active than the female, and the physical activity levels decreased as the age of the participants grow. In conclusion, it can be said that the physical activity level and physical fitness are correlated.